Respuesta :
Answer:
Option C.
Step-by-step explanation:
The given expression is ab - 2 = c
Option a : a = [tex]\frac{c}{b}[/tex] - 2
ab = c - 2b
Not equivalent to the original expression.
Option b : b = c + [tex]\frac{2}{a}[/tex]
ab = ac + 2 ⇒ [tex](\frac{ab-2}{a})[/tex] = c
Not equivalent
Option c : ab = c + 2
ab - 2 = c
Equivalent to original expression
Option d : a - [tex]\frac{c}{2}[/tex] = b
2a - c = 2b
Not equivalent
Option e : b - [tex]\frac{2}{c}[/tex] = a
bc - 2 = ac ⇒ c (b-a) = 2 ⇒ c = [tex]\frac{2}{b-a}[/tex]
Not equivalent
Option f : a = c + [tex]\frac{2}{b}[/tex]
ab = bc + 2
[tex](\frac{ab-2}{b} )[/tex] = c
Not equivalent